Panduan Sukses Pembangunan Rumah: Mengapa Anda Harus Menggunakan Analisis Biaya-Manfaat (Cost-Benefit Analysis): Penelitian - Laurent Damai Yanti Silaban; Gebatania Pakpahan; Titian Dhea Fresensia Purba; Bunga Madu Simanungkali; Jessica br Simanungkalit (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Housing development is a long-term investment that requires careful planning to avoid financial risks and unexpected cost escalation. This study highlights the importance of implementing Cost-Benefit Analysis (CBA) as a comprehensive assessment tool for evaluating the feasibility of residential construction projects. Using a descriptive qualitative approach, data were collected through literature review and documentation, and analyzed using key feasibility indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), Payback Period (PP), and Life Cycle Cost (LCC). The findings show that applying CBA provides a holistic understanding of the economic, social, and environmental benefits associated with the project, while also helping to minimize risks and optimize long-term investment value. Therefore, CBA serves as an essential instrument for ensuring that housing development projects are implemented effectively, efficiently, and sustainably.